Pengaruh Organizational Citizenship Behavior dan Kompeteni Profesional Terhadap Kinerja Guru - Suwarti (Journal of Innovation in Teaching and Instructional Media, 2025)
This study was conducted to determine: (1) the influence of Organizational Citizenship Behavior on teacher performance, (2) the influence of professional ability on teacher performance, (3) the influence of Organizational Citizenship Behavior and professional ability on teacher performance. The research method used was quantitative with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The subjects of the study were teachers of SMAN 1 Belitang with a sample size of 80 people taken using stratified proportional random sampling, the data were analyzed using path analysis after calculating the correlation of all research variables in matrix form. The results of this study indicate that Organizational Citizenship Behavior and professional ability have a positive and significant influence on teacher performance at SMAN 1 Belitang.